Safety Factor and Settlement Analysis of Borepile Foundation in Warmadewa Gianyar Hospital Building - Sinarta, I Nengah; Wisnawa, I Putu Gede Dharma; Sumanjaya, Anak Agung Gede (Civil and Environmental Science Journal (CIVENSE), 2024)
Building structure planning must be distinct from foundation structure planning. The foundation plays an important role in transferring building loads to the ground. The Warmadewa Gianyar Hospital building consists of 5 floors with a building area of 8323. 471 m2 on a granular soil location where there are three layers of soil types, namely sandy silt soil, silty sand, and sand mixed with rock grains. The Borepile foundation is installed at a depth of 12 m with an N SPT value of 60. This building carries dead loads, live loads, rain loads, wind loads, and earthquake loads. This building will use a bore pile foundation by modeling bore pile piles in GEO5 software to obtain safety factor values and installed reinforcement. Based on the analysis results, the pile diameter used is 450 mm and has a length of 12 m. The analysis obtained the carrying capacity with a safety factor of 2.1> 2 and a maximum settlement of 4.77 mm.